Use of Perennial Grasses in Peanut/Cotton Rotations: Effect on Pests - I. Small; D. L. Wright; J. J. Marois; S. George (EDIS, 2018)
SS-AGR-125, a 3-page fact sheet updated with I. Small, discusses the effect of perennial grasses on peanut and cotton nematode, disease and weed problems. Originally published by the UF Department of Agronomy, July 2006, this revision November 2018.